TLR7 Stimulation With Imiquimod Induces Selective Autophagy and Controls Mycobacterium tuberculosis Growth in Mouse Macrophages - Lee, Hyo-Ji; Kang, Su-Jin; Woo, Yunseo; Hahn, Tae-Wook; Ko, Hyun-Jeong; Jung, Yu-Jin (Frontiers in Microbiology, 2020)
Autophagy is a lysosomal self-digestion pathway that maintains internal homeostasis inside cells and critical process by which the innate immune system eliminates intracellular bacteria. In this study, we showed that stimulation of Toll-like receptor 7 (TLR7) with imiquimod (IMQ) triggered autophagic cell death in macrophages by enhancing the generation of reactive oxygen species (ROS) via the p38- or MEK/ERK1/2-mediated signaling pathway in the early phase. IMQ significantly increased mitochondrial ROS and targeted autophagosomes to the mitochondria. Stimulation of TLR7 with IMQ enhanced the expression of BNIP3, which was localized to mitochondria and interacted with beclin-1, leading to mitophagy. In addition, IMQ substantially induced NO production through the GSK-3β-mediated signaling pathway, which led to autophagy in the late stage. We further examined whether the induction of autophagy by IMQ effectively eliminated intracellular microbes. Macrophages were infected with a virulent Mycobacterium tuberculosis (Mtb) strain, H37Rv, and then treated with IMQ. IMQ suppressed intracellular Mtb growth by inducing autophagy in a dose-dependent manner and increased NO production. Inhibition of autophagy using 3-methyladenine (3-MA) prevented autophagosome formation and control of intracellular Mtb growth in macrophages. These findings revealed a novel mechanism by which IMQ induces selective autophagy to promote intracellular killing machinery against Mtb infection in macrophages.